The Study of External Pathologies in Fish of the South‐Western Coast of the Black Sea - T. V. Gavruseva (Юг России: экология, развитие)
Aim. The aim of our investigation was to study the possibility of using the visual pathologies of fish as biomarkers of pollution to identify those fish species most sensitive in this way as biological monitors in assessing the ecological state of Sevastopol waters.Material and Methods. 461 specimens of eleven common species of fish from the waters of Sevastopol were subjected to external examination and dissection in 2018. A semi‐quantitative gradation of the identified pathologies was conducted using the Health Assessment Index (HAI).Results. Twenty three types of visual pathology were recorded. Abnormalities in the skin and gills, fin alterations, skeletal deformities, pathologies of liver, spleen and gonads and parasitic invasions were noted. Analysis of external anomalies using the Health Assessment Index (HAI) revealed that the most potentially indicative species for visual biomonitoring were the following demersal fishes: knout goby Mesogobius batrachocephalus Pallas, 1814, round goby Neogobius melanostomus Pallas, 1814 and East Atlantic peacock wrasse Symphodus tinca Linnaeus, 1758. Liver changes detected in these three fish species may indicate chronic exposure and reaction to xenobiotics and the presence of ectoparasites would indicate a weakening of the immune status of the individual specimens studied.Conclusions. Pathological studies of fish in Sevastopol’s coastal zone indicated that the condition of their organs and tissues is related to environmental factors and that there are sensitivities to habitat pollution. The results of the study are of interest in the future development of monitoring programs for bioassays and bioindication of hydrobionts using fish as biomarkers.